HUBUNGAN ANTARA KONSEP DIRI DENGAN PENYESUAIAN DIRI GELANDANGAN DAN PENGEMIS DI PSBK PANGUDI LUHUR BEKASI - Habibullah Habibullah (Puslitbangkesos Kementerian Sosial RI, 2010)
This study aims to describe the self-concept, self adjustment and the relationship between self concept and adjustment of homeless people and beggars (gelandangan an pengemis/gepeng) on the Panti Sosial Bina Karya Pangudi Luhur. Therefore, this study used a quantitative approach that will be done by cross sectional. The samples in this study using simple random sampling method. The results showed that 1). 57% of